Warming reduces tall fescue abundance but stimulates toxic alkaloid concentrations in transition zone pastures of the U.S. - McCulley, Rebecca L.; Bush, Lowell P.; Carlisle, Anna E.; Ji, Huihua; Nelson, Jim A. (Frontiers in Chemistry, 2014)
Tall fescue pastures cover extensive acreage in the eastern half of the United States and contribute to important ecosystem services, including the provisioning of forage for grazing livestock. Yet little is known concerning how these pastures will respond to climate change. Tall fescue’s ability to persist and provide forage under a warmer and wetter environment, as is predicted for much of this region as a result of climate change, will likely depend on a symbiotic relationship the plant can form with the fungal endophyte, Epichloë coenophiala. While this symbiosis can confer environmental stress tolerance to the plant, the endophyte also produces alkaloids toxic to insects (e.g., lolines) and mammals (ergots; which can cause ‘fescue toxicosis’ in grazing animals). The negative animal health and economic consequences of fescue toxicosis make understanding the response of the tall fescue symbiosis to climate change critical for the region. We experimentally increased temperature (+3oC) and growing season precipitation (+30% of the long-term mean) from 2009 – 2013 in a mixed species pasture, that included a tall fescue population that was 40% endophyte-infected. Warming reduced the relative abundance of tall fescue within the plant community, and additional precipitation did not ameliorate this effect. Warming did not alter the incidence of endophyte infection within the tall fescue population; however, warming significantly increased concentrations of ergot alkaloids (by 30-40%) in fall-harvested endophyte-infected individuals. Warming alone did not affect loline alkaloid concentrations, but when combined with additional precipitation, levels increased in fall-harvested material. Although future warming may reduce the dominance of tall fescue in eastern U.S. pastures and have limited effect on the incidence of endophyte infection, persisting endophyte-infected tall fescue will have higher concentrations of toxic alkaloids which may exacerbate fescue toxicosis.